Communication Resilience in Enhancing Branding of SME Products: Implementation of Information Technology as a Strategic Innovation - Fachmi Ibrahim; Alma Mandjusri; Yoedo Shambodo (Jurnal Minfo Polgan, 2024)
SMEs play a vital role in the global economy, particularly in creating employment opportunities. SMEs often face challenges in building and strengthening their brand image. Limited resources and accessibility to a wider market are major obstacles. This research aims to examine communication resilience and the implementation of information technology in enhancing branding of SME products. This research method utilizes a qualitative approach with a focus on literature review and descriptive analysis. Data used are gathered from scholarly articles published between 2006 and 2024 through Google Scholar. The study results indicate that communication resilience is a crucial factor for SMEs in addressing challenges and changes in the business environment. The implementation of information technology as a strategic innovation plays a crucial role in strengthening this communication resilience. By leveraging digital platforms and social media, SMEs can enhance product visibility, engage with customers, and expand the market without substantial costs.